ANALISIS KESULITAN SISWA SMP KELAS VIII DAL AM MENYELESAIKAN SOAL POLA BILANGAN BERDASARKAN KEMAMPUAN PENALARAN MATEMATIK - Sagita Nur Ariyanti; Wahyu Setiawan (Journal on Education, 2019)
The purpose of this study was to determine the difficulties of students in solving the problem of mathematical reasoning abilities in the material pattern number. The method used in this study is descriptive qualitative which aims to describe students' difficulties in completing the number pattern material based on their mathematical reasoning ability. To obtain the research data, the instrument is used in the form of tests of mathematical reasoning abilities in the form of description tests and interviews. The place of research was carried out at Al-Barry Mts Cikalongwetan. The population in this study were all students of Al-Barry Mts who skipped a row, and the sample was the eighth grade students of Al-Barry's Mts in a row. Based on the analysis of the data obtained conclusions: 1) students have difficulty in determining the pattern on the question, 2) students have difficulty in formulating generalizations of regularity / pattern numbers, 3) students are too focused on the formula.